Education on Smoking Dangers for Dental and Oral Health Among Students - Widodorini, Trining; Fauzia, Malianawati; Lodra, Ester Handayani; Rafie, Mahardhika Ali; Hamidullah, Achmad Maulidana; Nayola, Adelia Marta; Adilah, Hanifa Fairuz; Wijanarko, Grace Vanesa; Alifah, Nisrina Andini; Fasa, Fathina Kamilia; Winara, Jesselyn; Aulia, Nabila Rizky Akbar (Caring: Jurnal Pengabdian Masyarakat, 2025)
Background: Cigarettes contain thousands of harmful chemicals that can cause oral health problems such as tooth discoloration, halitosis, gingivitis, and oral cancer. WHO (2019) reported that 19.2% of Indonesian adolescents aged 13–15 are smokers, while Riskesdas (2018) found 57.6% of Indonesians have oral health issues. Early education is essential to raise awareness of smoking hazards. Objective: To improve students’ understanding of the effects of smoking on oral and dental health at SMP Muhammadiyah 01 Malang. Methods: Conducted on July 17, 2024, this activity involved 7th–9th grade students using a pre-test and post-test design to measure knowledge before and after education delivered via video and presentation. Results: Knowledge scores increased significantly after the intervention, with most students showing good to adequate understanding. Conclusion: Health education effectively enhances students’ awareness of the dangers of smoking and the importance of oral health care.